Modelagem matemática da dispersão de plumas poluentes em aquíferos - Santos, Larisse Mendes dos (2015)
This work had as objectives, model and simulate the transport of pollutants in free aquifers. The model developed in this research uses permanent flow regime and transient transport system for pollutants. We used a model based on Eulerian advection-dispersion equation and Lagrangian model to help estimate of dispersivities to simulate the spatial and temporal distribution of the concentration of a generic pollutant in groundwater. The model built was based on the Finite Difference Method, applying the Crank Nicolson scheme, whose discrete equations were conveniently implemented in a computer language. For solution of the linear system, used the sparse storage of the coefficient matrix and the Biconjugate gradients method Pre-conditioning and stabilized (PBiCGSTAB). Therefore, the computer programs were used VBA (Visual Basic for Applications) and the Surfer10. The model application area is located in the urban area of the city of Araguari / MG, together with a hypothetical sources of pollution, punctual, diffuse and linear, disseminated in the urban area. Sensitivity analyzes were performed with the unknown parameters for the Bauru aquifer, noting the sensitivity of the model to the decay coefficient of the first order and the coefficients governing the longitudinal and transverse dispersivity. The results show that the model built satisfactorily presents the standard pollutant transport in groundwater, taking into account the exploitation of pollutants from the wells in an expansion thereof with spreading over the simulated years. The dispersion of pollutants down is influenced by the direction and sense of groundwater flow, with migration to cones of depression. An advantage of the model is implemented in this study the possibility of the simulation being performed in single individual computers without excessive consumption of time and using Excel as a base, a widespread practice of engineering on the program.